Study of synthesis parameters and photocatalytic activity of TiO2 nanostructures - Mahdi Shahrezaei (Journal of Experimental Nanoscience, 2017)
In this present study, various types of TiO2 nanostructures were synthesised via hydrothermal method from a commercial titanium dioxide. The effects of the initial concentration of titanium dioxide and the reaction time on the morphology of synthesised nanostructures were investigated. The TiO2 nanostructures were calcined at 500 °C and examined for the photocatalytic performance by decomposing formic acid as an organic pollutant. Scanning electron microscopy, transmission electron microscopy, Brunauer–Emmett–Teller and X-ray diffraction were employed to characterise the synthesised TiO2 nanostructures. The outcomes showed more influence of reaction time rather than initial TiO2 concentration on the properties of TiO2 nanostructures. Various TiO2 nanostructures such as, nanorods and nanotubes were fabricated at different initial TiO2 concentrations and reaction times. In addition, the synthesised nanorod structures showed higher photocatalytic activity than the nanotubes. This is owing to the presence of rutile–anatase combined crystalline phases in the nanorod structures.